Exploration of Javanese Children's Knowledge and Attitudes about Puberty and Reproductive Health - Indraswari, Ratih; Widjanarko, Bagoes; Shaluhiyah, Zahroh; Suryoputro, Antono; Musthofa, Syamsulhuda Budi (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Every year, adolescent pregnancy cases in Javanese society become challenging. Reproductive health education must be provided before the child enters puberty despite experiencing cultural barriers in its delivery. This study aims to explore children’s knowledge and attitudes about puberty and reproductive health to analyze the need for reproductive health education for children living in Javanese culture. This cross-sectional study sampled 174 children aged 9-11 years in the capital city of Central Java. Children in this study are female (54.6%) and male (45.4%), and 20.1% of them have already experienced puberty. As many as 48.9% of children have low knowledge, especially about puberty signs and menstruation. Most children have good attitudes about reproductive health, but 6.9% are permissive. There is no significant relationship between knowledge and attitudes (p-value=0.606). Puberty status is also unrelated to children’s knowledge (p-value=0.678) and attitudes (p-value=0.291). Permissive attitudes regarding adolescent pregnancy need to be highlighted. This is potentially harmful to children, especially if the child does not immediately engage in proper reproductive health education. The reproductive health educational model does not need to separate children’s classes based on their puberty status. The Ministry of Health and Education needs to improve children’s reproductive health knowledge by considering the character of Javanese society, which is still taboo.